Penerapan Kompres Kayu Manis Pada TN.S Dengan Gout Arthritis Untuk Mengurangi Tingkat Nyeri - Cholisa Resmi Sari; Siti Robeatul Adawiyah; M. Hasan Basri (Lembaga Pengembangan Kinerja Dosen, 2024)
Gouty arthritis is a metabolic disease that mostly occurs in middle-aged to elderly men and women in the post-menopausal period. This metabolic disease is caused by the accumulation of monosodium urate monohydrate crystals in the joints and connective tissue tophi. Joint pain is a problem for elderly people in the world and in Indonesia. It was recorded according to (WHO, 2023) that in 2019, around 528 million people worldwide suffered from joint pain, an increase of 113% since 1990. Around 73% of joint pain sufferers were over 55 years old, and 60% were women. With a prevalence of 365 million people, the knee is the joint most frequently affected, followed by the hip and hand. By using cinnamon as a non-pharmacological measure to reduce pain caused by signs and symptoms of gouty arthritis. Method: Case study using nursing care for Mr. S by doing a warm cinnamon compress for 7 days. Results and Conclusions: Chronic pain problems were resolved with warm cinnamon compresses marked by Mr. S said the pain had disappeared and he could carry out daily activities. P: pain caused by gout Q: none R: none S: 1 T: none. Mr. S still looks smiling and no longer grimacing, Mr. S doesn't seem anxious, Mr. S appears to be able to carry out activities and does not avoid pain. TTV results TD: 130/80 mmH N: 84x/m RR: 22x/m S: 36.6℃.